Implementing Transit Oriented Development Principles in Designing Light Rail Transit Station in Bandung - Fathya Itan Jeehan Widodo; Ciptadi Trimarianto; I Wayan Wiryawan (Journal of Architectural Research and Design Studies, 2020)
The density of transportation in Bandung has been increased every year which causes many problems and one of them is congestion. The low level of security, comfort, and long trip are the main factors of people preferring private vehicles over public transportation as a driving option. The form of public transportation that becomes a solution for Bandung city is Light Rail Transit (LRT) with the concept of transit-oriented development (TOD). TOD is an urban design in aiming to reduce mobility by integrating the role of mixed-use. This study using several variables that combined the theory of Cervero (1997) and ITDP (2014): walk, cycle, connect, transit, and design. The importance of applying TOD’s principle is interconnecting between transportation and various infrastructure in the selected area, such as commercial, office, residence, etc. The implementation of the TOD principle in LRT station design is adjusted to the characteristics and policies of selected area. The result gathered from this study is the design of supporting facilities of transit area that meets TOD principles by ITDP in a way to aim walkable city for Bandung better urban mobility.Keywords: connectivity; LRT; TOD; transportation.